Self-consistent magnetohydrodynamic simulation of jet launching in a neutron star: white dwarf merger - Morán Fraile, Javier; Röpke, Friedrich; Pakmor, Rüdiger; Aloy, Miguel A.; Ohlmann, Sebastian T.; Schneider, Fabian; Leidi, Giovanni; Lioutas, Georgios (Astronomy and astrophysics, 2024)
The merger of a white dwarf (WD) and a neutron star (NS) is a relatively common event that produces an observable electromagnetic signal. Furthermore, the compactness of these stellar objects makes them an interesting candidate for gravitational wave (GW) astronomy, potentially being in the frequency range of LISA and other missions. To date, three-dimensional simulations of these mergers have not fully modeled the WD disruption or have used lower resolutions and have not included magnetic fields even though they potentially shape the evolution of the merger remnant. In this work, we simulated the merger of a 1.4 M⊙ NS with a 1 M⊙ carbon oxygen WD in the magnetohydrodynamic moving mesh code AREPO. We find that the disruption of the WD forms an accretion disk around the NS, and the subsequent accretion by the NS powers the launch of strongly magnetized, mildly relativistic jets perpendicular to the orbital plane. Although the exact properties of the jets could be altered by unresolved physics around the NS, the event could result in a transient with a larger luminosity than kilonovae. We discuss possible connections to fast blue optical transients (FBOTs) and long-duration gamma-ray bursts. We find that the frequency of GWs released during the merger is too high to be detectable by the LISA mission, but suitable for deci-hertz observatories such as LGWA, BBO, or DECIGO.